Sweet syndrome presenting late after non Hodgkin’s lymphoma and dermatomyositis - Olguín Ramírez, Leticia Alejandra; Jaime Pérez, José Carlos; Mendoza Rodriguez, Cynthia; Gómez Almaguer, David (UANL. Facultad de Medicina, 2014)
Abstract Sweet syndrome is a rare neutrophilic dermatosis consisting in the onset of high fever, neutrophilia, and typical painful skin lesions including erythematous papules, nodules, and plaques on the face, trunk, and extremities, with a bilateral and asymmetrical pattern. Sweet syndrome is classiied as idiopathic, predominating in women; malignancy-associated, mainly with hematological cancer, and drug-induced. The diagnosis is based on clinical history and skin manifestations, being conirmed by a complete blood count showing neutrophilic leukocytosis, and speciic indings in the skin biopsy. We report the case of a 68 year-old man with a 10-year evolution of dermatomyositis complicated by lung ibrosis, followed 8 years later by non-Hodgkin lymphoma (NHL) accompanied by worsening of his ibrosis. Two years after the successful treatment of NHL the patient developed an acute episode of severe dyspnea, multiple skin lesions, and 95% neutrophilia. At that time the patient had a severe lung function impairment complicated by nosocomial pneumonia that led to his death, a few days after the diagnosis of Sweet syndrome was established by histopathology examination. Sweet syndrome is a rare dermatologic entity that can appear several years after diseases characterized by immune dysfunction such as dermatomyositis and NHL.